2017
DOI: 10.1111/bju.14058
|View full text |Cite
|
Sign up to set email alerts
|

Early discharge and post‐discharge outcomes in patients undergoing radical cystectomy for bladder cancer

Abstract: Early discharge after RC was not associated with increased readmissions or post-discharge complications. Future prospective studies, with defined peri-operative care pathways, are needed to identify potential components that may enable hospitals to discharge patients early without compromising post-discharge outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
(33 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, subgroup analysis in the publication by Xia et al ( 3 ) revealed that the odds of readmission after early discharge were the same for all subsets of patients except for patients aged ≥85 years. Although the impact of age on outcome is of importance it needs to be emphasized that these data should be interpreted with caution, as only 89 patients included in the analysis were aged ≥85 years of whom 20 patients were discharged early.…”
mentioning
confidence: 97%
See 4 more Smart Citations
“…Furthermore, subgroup analysis in the publication by Xia et al ( 3 ) revealed that the odds of readmission after early discharge were the same for all subsets of patients except for patients aged ≥85 years. Although the impact of age on outcome is of importance it needs to be emphasized that these data should be interpreted with caution, as only 89 patients included in the analysis were aged ≥85 years of whom 20 patients were discharged early.…”
mentioning
confidence: 97%
“…Xia et al assessed whether discharging patients early after RC is associated with an increased risk of readmission and post-discharge complications ( 3 ). Based on a retrospective analysis of the National Surgical Quality Improvement Program database they concluded that early discharge can be performed safely in a subgroup of patients after RC.…”
mentioning
confidence: 99%
See 3 more Smart Citations